Unpacking the Effect of Organizational Silence on Teachers' Turnover Intention: The Mediating Role of Work Alienation - Katitas, Sevda (SAGE PUBLICATIONS INC, 2026)
This study investigates the mediating role of work alienation in the relationship between organizational silence and teachers' turnover intention within the context of a developing country. Drawing on data from 707 teachers across nine provinces in T & uuml;rkiye, the study adopts a cross-sectional correlational design and employs structural equation modeling for analysis. The findings indicate that organizational silence significantly contributes to teachers' turnover intention, both directly and indirectly through heightened work alienation. These dynamics represent critical challenges for the sustainability and quality of educational systems, particularly in middle-income countries where teacher retention remains a pressing policy concern. By highlighting the structural and relational factors influencing teacher attrition, the study offers valuable insights for education policymakers and stakeholders aiming to strengthen teacher engagement and long-term development goals in the education sector.
Keywords: organizational silence; work alienation; turnover intention; teacher retention; EMPLOYEE SILENCE; COMMITMENT; SCHOOL; ANTECEDENTS; IMPACT; LEARN; DETERMINANTS; PERSONALITY; INVOLVEMENT; PREDICTORS; Social Sciences - Other Topics